1996
DOI: 10.1111/j.1476-5381.1996.tb15568.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the endothelium in the relaxation of the leopard frog (Rana pipiens) aorta in response to acetylcholine

Abstract: 1 The vasodilator response to acetylcholine (ACh) was investigated in the aortic arches of the leopard frog (Rana pipiens). 2 With adrenaline pre-constricted preparations, both ACh and sodium nitroprusside (SNP) caused concentration-dependent relaxations. Damage to the endothelial layer abolished relaxations to ACh, or reduced them greatly, but had no effect on vasodilatation to SNP.3 NG-Nitro-L-arginine methyl ester (L-NAME; 1 -100 gM) concentration-dependently inhibited relaxations in response to ACh, but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Staining also was found in areas outside the CNS (see Fig. 7), where NO is known to be located and to play a functional role in amphibians, namely, the skin (Neumann et al, 1996), the blood vessels (Knight and Burnstock, 1996), and the eyes (Savchenko et al, 1997). This further supports the proposal that NADPH-d labels NOS and suggests that the NADPH-d technique also identifies discrete regions of the CNS where NO is playing a functional role early in development.…”
Section: Discussionsupporting
confidence: 70%
“…Staining also was found in areas outside the CNS (see Fig. 7), where NO is known to be located and to play a functional role in amphibians, namely, the skin (Neumann et al, 1996), the blood vessels (Knight and Burnstock, 1996), and the eyes (Savchenko et al, 1997). This further supports the proposal that NADPH-d labels NOS and suggests that the NADPH-d technique also identifies discrete regions of the CNS where NO is playing a functional role early in development.…”
Section: Discussionsupporting
confidence: 70%
“…Many studies in non-mammalian vertebrates (birds, reptiles, amphibians and teleost fishes) have shown that NO mediates vasorelaxation (Olson and Villa, 1991;Knight and Burnstock, 1993;Knight and Burnstock, 1996;Nilsson and Soderstrom, 1997; Martinez-Lemus et al, 1999; Crossley et al, 2000; Axelsson et al, 2001;Broughton and Donald, 2002;Jennings et al, 2004;Broughton and Donald, 2005;Galli et al, 2005;Skovgaard et al, 2005), but there is some controversy as to whether the vascular endothelium synthesises and releases NO in fishes and amphibians. A number of studies have provided evidence that endothelial NO signalling is present in the vasculature of fishes (Mustafa and Agnisola, 1998;Fritsche et al, 2000;Pellegrino et al, 2002) and amphibians (Rumbaut et al, 1995;Knight and Burnstock, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have provided evidence that endothelial NO signalling is present in the vasculature of fishes (Mustafa and Agnisola, 1998;Fritsche et al, 2000;Pellegrino et al, 2002) and amphibians (Rumbaut et al, 1995;Knight and Burnstock, 1996). In contrast, in many species of teleost and elasmobranch fishes, there is physiological and anatomical evidence that an endothelial NO system is absent from the vasculature, and that the endothelium-derived relaxing factor is in fact a prostaglandin (Olson and Villa, 1991;Evans and Gunderson, 1998;Miller and Vanhoutte, 2000;Park et al, 2000;Donald et al, 2004;Jennings et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Early comparative studies in avian (Hasegawa and Nishimura, 1991), reptilian (Knight and Burnstock, 1993), and amphibian (Rumbaut et al, 1995;Knight and Burnstock, 1996) species provided evidence that an endothelial NO system was present. Furthermore, there is evidence for endothelial NO signalling in teleost fish, which was obtained in perfused vascular beds in which vascular resistance was affected by the NO precursor L-arginine, and inhibition of NO synthase, the enzyme that generates NO (Nilsson and Söderström, 1997;Mustafa et al, 1997;Mustafa and Agnisola, 1998).…”
mentioning
confidence: 99%